Do Women on Boards Really Impact Firm Growth? - Ulfa Rahmawati; Erna Fitri Komariyah (Universitas Teknologi Yogyakarta, 2023)
The issue of gender equality is one part of Indonesia's SDGs target. Gender equality refers to equality between men and women in fulfilling rights and obligations. One of the targets of Indonesia's SDGs for gender equality is to strengthen policies and legislation to increase gender equality and women's empowerment. These situations unquestionably impact the influence of women on board. This study examines the growth of LQ 45 businesses in Indonesia in connection to the number of female directors. This study was conducted using quantitative research approaches. In Indonesia, between 2019 and 2021, 34 LQ45 companies were chosen for the sample utilizing purposeful selection. This study shows that the presence of women on the board of directors will not have a favourable effect on the LQ 45 firm's growth in Indonesia between 2019 and 2021.